Genre cinema and cinema Sui Generis: Adrian Piotrovsky and cinema taxonomy. Issue 1 (2nd January 2022) - Bird, Robert
ABSTRACT: Although 'Towards a Theory of Cine-Genres' announces his interest in connecting film genre to the formal properties of the medium, Adrian Piotrovsky's thinking as a whole is marked by a fundamental ambivalence to genre. Placing this better-known essay within the overall development of his thinking on cinema reveals how Piotrovsky grappled with taxonomizing cinema and refined a vision for a Soviet filmmaking that moved beyond the limitations of genre.